The occurrence of the pseudoplanktonic crinoids Pentacrinites and Seirocrinus from the Early Jurassic Toyora Group, western Japan - Hunter, Aaron; Oji, T.; Okazaki, Y. (BioOne, 2011)
We document the occurrence of three species of Jurassic crinoids from the Lower Jurassic Toyora Group (Yamaguchi Prefecture), western Japan, belonging to the genera Pentacrinites and Seirocrinus. The former is found for the first time in Japan. This find extends the range of Pentacrinites into Eastern Eurasia. These species can be confidently assigned to Pentacrinites dichotomus (McCoy, 1848), P. cf. doreckae Simms (1989), and Seirocrinus subangularis (Miller, 1821). Pentacrinites and Seirocrinus are well known genera in the Lower Jurassic of Europe, with identical species occurring in the British Lias of Yorkshire and the Posidonienschiefer of southern Germany. Furthermore, previous studies have established that the taphonomy, sedimentology and palaeoenvironmental context of the Toyora Group, at least in the Nishinakayama Formation, are comparable to those of the European Boreal and Tethyan shallow seas including the occurrence of oxygen-depleted bottom conditions. Thus, the paraautochthonous preservation and wide geographic range of these species, as well as the associated fauna, suggest a possible pseudoplanktonic lifestyle for both Pentacrinites and Seirocrinus in the Early Jurassic of Japan. The ‘Hiemer’ specimen kept in the University of Göttingen is designated herein as the neotype of Seirocrinus subangularis.